2010
DOI: 10.1103/physreve.81.011119
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of a one-dimensional driven-diffusive system and an equilibrium two-dimensional walk model

Abstract: It is known that a single product shock measure in some of one-dimensional driven-diffusive systems with nearest-neighbor interactions might evolve in time quite similar to a random walker moving on a one-dimensional lattice with reflecting boundaries. The non-equilibrium steady-state of the system in this case can be written in terms of a linear superposition of such uncorrelated shocks. Equivalently, one can write the steady-state of this system using a matrix-product approach with two-dimensional matrices. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…for l = 1, · · · , N (17) in which only the lth element is non-zero and equal to one. If we write the partition function (14) as…”
Section: The Transfer Matrix Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…for l = 1, · · · , N (17) in which only the lth element is non-zero and equal to one. If we write the partition function (14) as…”
Section: The Transfer Matrix Methodsmentioning
confidence: 99%
“…Apart from these approaches one can try to connect the matrix representation of the algebra of a one-dimensional reaction-diffusive system directly to the transfer matrix of an equilibrium two-dimensional walk model. In this way the one can actually show that the normalization coefficient of the stationary distribution function of the non-equilibrium system coincides with the partition function of an equilibrium walk model [15][16][17]. In this paper we consider the PASEP with open boundaries where the steady-state of the system can be written in terms of a linear superposition of product measures with a finite number of shocks.…”
Section: Introductionmentioning
confidence: 99%
“…It is also useful to interpret Z(z) as the generating function for a model of weighted lattice paths [31][32][33][34][35][36] , which gives some insight into the PASEP phase diagram. From this point of view the tridiagonal matrix C in the particular representation of equ.…”
Section: The Pasep and Lattice Pathsmentioning
confidence: 99%
“…Over the last couple of years there has been a growing interest in studying of the connections between the one-dimensional driven-diffusive systems and the twodimensional walk models [1][2][3][4]. It has been shown that a properly defined steady-state normalization factor, called the partition function, of some of the one-dimensional driven-diffusive systems with open boundaries obtained using a matrix product method (reader can see [5] for a review) is equal to the partition function of a twodimensional walk model obtained using a transfer matrix method [1,6,7]. It is known that the one-dimensional driven-diffusive systems exhibit a variety of interesting critical behaviors, such as non-equilibrium phase transition and realspace condensation, by changing their microscopic reaction rates.…”
Section: Introductionmentioning
confidence: 99%